2016
DOI: 10.1007/s00348-016-2199-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a separated flow response to localized and global-type disturbances

Abstract: to generate very similar Lagrangian flow structures. The results suggest a certain degree of universality in the POD modes/flow structures for the separated flow over an airfoil, irrespective of the type of excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In addition, Monnier et al (2016) reported that the circulatory force on a wing in response to an impulse-like pitching motion also follows the same lift reversal behavior as the AFC actuators (e.g. synthetic and burst-blowing jets).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, Monnier et al (2016) reported that the circulatory force on a wing in response to an impulse-like pitching motion also follows the same lift reversal behavior as the AFC actuators (e.g. synthetic and burst-blowing jets).…”
Section: Introductionmentioning
confidence: 92%
“…Next we apply the Proper Orthogonal Decomposition (POD) to the transient case of the single burst actuation to gain additional insight into the modes that are responsible for the lift and pitching moment reversal. In a similar experiment, Monnier et al (2016) reported that the temporal coefficient of the second Proper Orthogonal Decomposition (POD) mode correlates with the negative of the lift coefficient variation following a singleburst input. The POD method can reduce a large number of interdependent variables to a much smaller number of independent modes, while retaining as much as possible the variation in the original variables (Kerschen et al 2005).…”
Section: Proper Orthogonal Decomposition (Pod) Of the Flow Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…8, the time delay to reach the maximum lift increment depends on the separated flow dynamics, and not on the type of actuation. The initial time delay is the time required for the shear-layer perturbation to evolve into a large-scale vortex that convects over the surface [48,56]. Therefore, it is the fluid dynamic response of the shear layer and separated region that determines the lift response time: not the actuator.…”
Section: A System Response To An Actuator Pulsementioning
confidence: 99%
“…13,14 Holmes 15 designed a wind tunnel capable of generating the sinusoidal streamwise gust with the movement of the tunnel wall. Granlund et al 16 and Monnier et al 17 and Kerstens et al 18 and Strangfeld et al 8 obtained the sinusoidal streamwise gust by oscillating the free stream with the louvers system. These scholars observed deviations in unsteady lift amplitudes and phases from theoretical predictions at high reduced frequencies or at large angles of attack.…”
mentioning
confidence: 99%